KRITIK RELIGIUS QOHELET (Pkh 4: 17-5: 6) (Semio-structural Approach) - Isaak, Servulus (LOGOS, 2004)
Since last few decades biblical scholars introduce the so called â€˜synchronic reading of the textâ€™ as a method of interpretation. Some tend to call it holistic interpretation, others prefer to call it â€˜aesthetic approachâ€™, assuming that the Bible is a sort of artistry work based on the linguistic principles and philosophy of language. This approach goes to various directions such as narrative analysis, structuralism and a more simple structural analysis. Without undermining the validity of historic-critical method with its various steps of interpretation, this article aims to analyze Qoh 4: 17-5: 6 applying to some extend the semio-structural analysis. Scholars are debating on the notion of various terminologies applied in this approach. Hence, we will focus only on some basic linguistic concepts, without going too far into the complicated analysis of semiotic quadratic configuration, which would go beyond our purpose. Syntactic, argument, paradigmatic and semantic analysis in this article lead to highlight the universal semantic of the text. â€œFear God!â€ is the key and the important capstone to understand the whole book of Qohelet, particularly the universal semantic of the pericope under analysis.